Next generation sequencing reveals widespread trypanosome diversity and polyparasitism in marsupials from Western Australia. Issue 1 (April 2018) - Cooper, Crystal; Keatley, Sarah; Northover, Amy; Gofton, Alex W.; Brigg, Frances; Lymbery, Alan J.; Pallant, Louise; Clode, Peta L.; Thompson, R.C. Andrew
Abstract: In Western Australia a number of indigenous Trypanosoma spp. infect susceptible native marsupials, such as the woylie ( Bettongia penicillata ), brushtail possum ( Trichosurus vulpecula ), and chuditch (Dasyurus geoffroii ). Two genotypes of Trypanosoma copemani (identified as G1 and G2) have been found in the woylie, and G2 has been implicated in the decline of this host species, making its presence of particular interest. Here we used targeted amplicon next generation sequencing (NGS) of the Trypanosoma 18S rDNA loci on 70 Trypanosoma -positive marsupial blood samples, to identify T. copemani genotypes and multiple Trypanosoma infections (polyparasitism) in woylies and cohabiting species in Western Australia. Polyparasitism with Trypanosoma spp. was found in 50% of the wildlife sampled, and within species diversity was high, with 85 zero-radius operational taxonomic units (ZOTUs) identified in nine putative parasite species. Trypanosoma copemani was assigned 17 ZOTUs and was identified in 80% of samples. The most abundant ZOTU isolated (63%) differed slightly from the published genotype of G1, and G2 was the second most abundant ZOTU (14%). Trypanosome diversity was significantly greater in woylies than in brushtail possums, and parasite community composition also differed significantly between these host species. One novel Trypanosoma spp. genotype ( Trypanosoma sp. ANU2) was found in 20% of samples. A species of Crithidia was detected in a woylie, and two avian trypanosomes ( Trypanosoma avium and Trypanosoma sp. AAT) were identified in woylies for the first time. Graphical abstract: Image 1 Highlights: Extensive trypanosome diversity and polyparasitism in south Western Australia. A significant difference between trypanosomes infecting woylies and brushtail possums. Evidence that the current species-level taxonomy of Australian trypanosomes may need revision.